General Practitioners' Perspectives on Identifying Early Symptoms for Breast Cancer Detection in the Primary Care Facilities: A Case Study - Andinata, Bob (Kesmas, 2025)
In primary care settings, general practitioners (GPs) frequently face challenges in identifying the early symptoms of breast cancer. This study aimed to explore, in depth, the perspectives of GPs regarding the identification and interpretation of early-stage breast cancer symptoms during the early detection process in primary care facilities. This study used a qualitative approach based on a case study. Data were collected through in-depth interviews with GPs at primary health care and private clinics in Depok City, Indonesia, complemented by observations and documentation. The data was analyzed using the Miles and Huberman method. The questionnaire assessment and focus group discussion findings revealed that only 3.8% of GPs demonstrated good responses of understanding early and late-stage breast cancer symptoms. Most participants (82.7%) provided fair responses, whereas 13.5% provided poor responses, indicating significant gaps in clinical understanding and highlighting the need for improved training and clearer diagnostic guidance. In conclusion, GPs in primary care facilities tend to have general knowledge of breast cancer but lack the ability to distinguish specific early-stage symptoms from those of more advanced stages.